Crossing Borders Governing Environmental Disasters in a Global Urban Age in Asia and the Pacific (Springer Singapore, 2018)
This multidisciplinary book examines the diverse ways in which environmental disasters with compounding impacts are being governed as they traverse sovereign territories across rapidly urbanising societies in Asia and the Pacific. Combining theoretical advances with contextually rich studies, the book examines efforts to tackle the complexities of cross-border environmental governance. In an urban age in which disasters are not easily contained within neatly delineated jurisdictions, both in terms of their interconnected causalities and their cascading effects, governance structures and mechanisms are faced with major challenges related to cooperation, collaboration and information sharing. This book helps bridge the gap between theory and practice by offering fresh insights and contrasting explanations for variations in transboundary disaster governance regimes among urbanising populations in the Asia-Pacific.